Left Ventricular Function and Clinical Outcome among Patients with Peripartum Cardiomyopathy (Tanzania Medical Journal, 2009)
Background: Peripartum cardiomyopathies are endemic in Sub-Sahara Africa, causing a high morbidity and mortality. The effect of the recent introduction of Angiotensin converting enzyme inhibitors [ACEI] and beta-adrenergic blockers in the treatment of heartfailure is not well known in patients with peripartum cardiomyopathy in our set up.Objective: To determine the left ventricular function and clinical outcome of patients with peripartum cardiomyopathy after treating them with ACEI ,beta-adrenergic blockers and diuretics. Study Design: A descriptive prospective hospital based studyStudy Setting: Hindu Mandal Hospital in Dar es Salaam ,Tanzania Main OutCome Measures: Echocardiographic features useful in assessing patients with peripartum cardiomyopathy; clinical outcome as well as mortality after treatment with the current therapy of heartfailure Subjects: Sixty four consecutive patients with provisional diagnosisof peripartum cardiomyopathy who were referred to a cardiac clinic at Hindu Mandal Hospital.Interventions: A detailed past and present medical history, clinical examination as well as echocardiographic evaluation were performed. After initiating treatment, patients were followed up for twelve months. Results: Using echocardiography the left ventricular end-diastolic diameter at baseline was 65 + 6mm (range 55 to 78 mm) and the left ventricular fractional shortening was 17. 0 + 5.0% (range 7.0- 31.0%). At 12 months ejection fraction improved from 30 + 12 to 45 + 15% (p=0.0001). Five types of outcome were observed aftertaking the current medical treatment for heart failure for one year:(a) Complete remission in 35 (54.7%) patients (b) Incomplete remission in 13 (20.3%) patients (c)Absence of remission in 4 (6.3%) patients (d) Lost during follow up in 7 (10.9%) patients and (e) Deathin 5 (7.8%) patients. An initial ejection fraction below 30% and left ventricular end-diastolic dimension 6.0cm or greater, at the time of diagnosis were associated with more than 2 fold increased risk of incomplete/absence of remission when compared with those who hadcomplete remission. Conclusion: The addition of ACE inhibitors and B-adrenergicblockers to the therapy of peripartum cardiomyopathy led to a better clinical outcome compared with earlier reports. Left ventricular echocardiographic parameters provide significant prognostic information regarding recovery of cardiac function in patients withperipartum cardiomyopathy. Tanzania Medical Journal Vol. 23 (2) 2008: pp. 1-4